Evaluación del comportamiento de nanomateriales obtenidos a partir de botellas pet para la reducción del volumen de filtrado en un fluido de perforación base agua. (2021)
Currently, the disposal of plastic waste without a proper process to accelerate degradation or subsequent recycling is not feasible. Therefore, the investigations are focused on providing a solution to this is issue. Nanotechnology have driven the conversion of various materials to nanometric scales that can perform many functionalities to create and improve products, technologies or manufacturing processes. This project proposes the use of nanomaterials synthesized through the Chemical Vapor Deposition (CVD) technique to reduce the filtration volume of a water-based drilling fluid. To carry out the synthesis of nanomaterials was implemented polyethylene terephthalate (PET) as a carbon source, which was obtained through the alkaline hydrolysis procedure.